EXPERIMENTAL INVESTIGATION ON THE VARIABILITY OF THE DYNAMIC RESPONSE OF ASSEMBLIES OF NOMINALLY IDENTICAL COMPONENTS - H. H. Silva, Jorge; T. Fabro, Adriano (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Usually, structures contain inherent variability in geometric and material properties due to the complexity of manufacturing process. This variability, combined with components and subcomponents assemble uncertainties, provide relevant changes in the structure dynamic behavior with respect to the nominal design. Therefore, including those uncertainties in the dynamic analysis provides a wider range of response predictions improving structure reliability and hence reducing costs of design. A stochastic modelling is required to add these variabilities on the solution and probabilistic approaches are commonly used with Finite Element Analysis (FEA) to represent those uncertainties in dynamics analysis, named Stochastic FEA (SFEA). In this work, nominally identical structural components, built-up from beams and plates, are characterized from frequency response function measurements and natural frequencies. Some of their statistics, like histograms and percentiles, are then calculated. Then, some of these nominally identical structures are assembled and the variability of the dynamic response is investigated under the different possible permutations. Results are compared towards the existence of possible permutations leading to decreased or increased variability on the response of the assembly.